Candiru—a little fish with bad habits: Need travel health professionals worry?: A review - Bauer, Irmgard (Wiley-Blackwell Publishing, Inc., 2013)
Background: Over the last 150 years, a little South American fish with alleged unsavory habits has become the stuff legends are made of. With growing visitor numbers to the Amazon basin, the question of whether the animal poses a threat to the many travelers to the region arises. Methods: Scientific literature was identified by searching MEDLINE, ScienceDirect, ProQuest, and Google Scholar. The reference lists of all obtained sources served to refine the search, including the original historical writings where obtainable. Nonscientific material was discovered through extensive web searches. Results: First, the current popular understanding of the fish and its interaction with humans are presented followed by an overview of the historical literature on which this understanding is based. Next, the fish and its supposed attraction to humans are introduced. Finally, this review queries the evidence current medical advice utilizes for the prevention of attacks and the treatment of unfortunate hosts. Conclusions: Until evidence of the fish’s threat to humans is forthcoming, there appears to be no need for considering the candiru in health advice for travelers to the Amazon.